POLITICS OF LAW LIMITATION OF OWNERSHIP RIGHTS TO LAND AGRICULTURE IN NATIONAL AGRARIAN LAW - Rr. Widyarini Indriasti Wardani; Sigit Irianto (UNTAG Law Review, 2020)
Agricultural Land is a land that is intended or suitable for farming land to produce agricultural or livestock. The history of regulations on the limitation of ownership of agricultural land rights includes 2 periods, namely the limitation of ownership of land rightsduring the colonial period and the period after independence. The political and legal factors of the government greatly influence the operation of law in society, including in the implementation of land reform, especially the ownership of agricultural land rights,including restrictions on ownership of agricultural land rights. The politics of law applied in a government affects the implementation and enforcement of laws and regulations, changes in government that have occurred in Indonesia from the days of President Soekarno, President Soeharto, and Susilo Bambang Yudhoyono to President Joko Widodo affect the implementation of restrictions on ownership of agricultural land rights. The politics of land law are related to limiting ownership of rights to agriculture. It is hoped that the government will take sides by regulating the focus of ownership of agricultural land rights for the benefit of all Indonesian people, especially for farmers to own agricultural land. Ownership and control of agricultural land are not owned and controlled by certain groups or individuals.